2015
DOI: 10.1139/bcb-2015-0066
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and damage to erythrocytes in patients with chronic obstructive pulmonary disease — changes in ATPase and acetylcholinesterase activity

Abstract: The study indicates, for the first time, the changes in both ATPase and AChE activities in the membrane of red blood cells of patients diagnosed with COPD. Chronic obstructive pulmonary disease (COPD) is one of the most common and severe lung disorders. We examined the impact of COPD on redox balance and properties of the membrane of red blood cells. The study involved 30 patients with COPD and 18 healthy subjects. An increase in lipid peroxidation products and a decrease in the content of -SH groups in the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…On the other hand, high oxidative stress and free radicals can increase AChE activity [ 53 , 54 ]. Dal Forno et al [ 55 ] suggested that an increment in ROS formation and a significant increase in lipid peroxidation could lead to the exposure of the more active sites of the AChE.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, high oxidative stress and free radicals can increase AChE activity [ 53 , 54 ]. Dal Forno et al [ 55 ] suggested that an increment in ROS formation and a significant increase in lipid peroxidation could lead to the exposure of the more active sites of the AChE.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, ROS (O°⋅, H 2 O 2 , and OH - ⋅) can inhibit EPO synthesis, by mimicking a false O 2 signal in the renal peritubular interstitial cells. Oxidative stress can also increase the fragility of erythrocytes, decrease the amount of erythroid maturation, and reduce red cell survival ( Sailaja et al, 2003 ; Olszewska et al, 2012 ; Lang et al, 2014 ; Bukowska et al, 2015 ). ROS also mediate the inhibitory effect of proinflammatory cytokines on erythroid precursor proliferation ( Prince et al, 2012 ).…”
Section: Pathogenesis Of Cancer Related Anemiamentioning
confidence: 99%
“…Our recent study indicated changes in the activity of antioxidant enzymes in COPD patients. We observed an increase in the activity of glutathione peroxidase and a decrease in the activity of superoxide dismutase, but not in the activity of catalase activity [49]. However, Nadeem et al , Gumral et al and Woźniak et al observed changes in activity of all three enzymes – CAT, GSH-PX and SOD [5052].…”
Section: Discussionmentioning
confidence: 94%